“I’m Appalled and Astonished”: Experiences of Black Parents and Caregivers Navigating Early Learning and Childcare in Kingston and London, Ontario - Ajayi, Mary; Siiba, Alhassan; Kangmennaang, Joseph; Macdonald, Danielle; Luginaah, Isaac (Journal of Childhood Studies, 2026)
Access to nurturing early learning and childcare (ELCC) and a supportive early childhood environment play critical roles in promoting children’s cognitive, social, and behavioral development. However, access to these relevant programs and services remains inequitable, especially for historically marginalized communities, such as Black people. This paper reports the experiences of Black parents (n=25) as they navigated ELCC in Kingston and London, Ontario. Findings highlight four interrelated themes: systemic barriers in accessing ELCC services, lack of access to information and community support, cultural insensitivity at ELCC spaces, and socioeconomic challenges with accessing ELCC. The paper concludes with suggestions of actionable strategies to build trust and reorient the ELCC system to serve all children.